Dextranomer-Hyaluronic Acid and Polyacrylate-Polyalcohol Copolymer are Equally Efficient for Endoscopic Treatment of Vesicoureteral Reflux in Children - Bele, Uros; Bratus, Dejan (Urology Journal, 2019)
Purpose: To compare the efficacy of two bulking agents, Dextranomer-Hyaluronic Acid (DxHA) and Polyacrylate-Polyalcohol Copolymer (PPC) used for endoscopic treatment of vesicoureteral reflux (VUR). Materials and Methods: We endoscopically treated 125 patients (89 girls and 36 boys) diagnosed with VUR grades I-V, comprising a total of 174 refluxing ureters (RUs). Patients were categorized into two groups, 99 (56,9%) RUs were treated with DxHA (Group 1) and 75 (43,1%) RUs with PPC (Group 2). RUs treated with both bulking agents were excluded. The success of treatment was evaluated with postoperative VCUG at 3- and 12-months after the endoscopic procedure, only complete resolution of VUR was considered as treatment success. Data was collected and analyzed retrospectively. Statistical calculations were performed using the Chi-square test. Results: After a single injection 80,0% (60/75) and 68,7% (68/99 RUs) of RUs resolved completely when treated with PPC and DxHA, respectively (P = .094). A second injection of PPC healed another 10 RUs (total 93,3%), whereas DxHA resolved additional 16 RUs (total 84,8%) (P = .097). A third injection was needed for 1 RU, treated with PPC and another 3 RUs with DxHA. Twelve months post-operatively, we achieved a total resolution rate of 94,7% (71/75 RUs) with PPC, while DxHA successfully treated 87,9% (87/99) of RUs (P = .125). Conclusions: DxHA and PPC showed no statistically significant differences neither in the number of injections needed nor in the total success rate after 12 months of follow-up.